Challenges of cardiac sarcoidosis - Strambu, Irina R. (Frontiers in Medicine, 2023)
Sarcoidosis is a multisystem granulomatosis of unknown origin, which can involve almost any organ. Most frequently the disease involves the lungs and mediastinal lymph nodes, but it can affect the skin, the eyes, nervous system, the heart, kidneys, joints, muscles, calcium metabolism, and probably any other anecdotical organ involvement. Cardiac sarcoidosis is one of the most challenging involvements, as it can lead to cardiac mortality and morbidity, and also because the diagnosis may be difficult. With no specific symptoms, cardiac sarcoidosis may be difficult to suspect in a patient with no previous extra-cardiac sarcoidosis diagnosis. This manuscript reviews the current knowledge of the diagnosis and decision to treat cardiac sarcoidosis, and illustrates the information with a case presentation of a young adult with no risk factors, no previous diagnosis of sarcoidosis, and with cardiac symptoms impairing his quality of life.